yang Pengaruh Dimensi Pemasaran Media Sosial terhadap Niat Beli Konsumen terhadap Produk Pakaian Olahraga di Platform E-Commerce Shopee - Muhammad Farras Radhi; Mochammad Yudha Febrianta (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of Social Media Marketing Content, Consumer Engagement and Interaction, Brand Awareness, and Influencer Marketing on the purchase intention of sportswear products on Shopee. Using a quantitative approach, data were collected from 200 digital-native consumers and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). Results confirm that all four variables significantly enhance purchase intention, with content quality emerging as the primary driver. These findings imply that sportswear retailers should integrate interactive community features and strategic influencer partnerships to build brand trust and optimize conversion pipelines, ultimately securing a sustainable competitive advantage in social commerce. Keywords: Social Media Marketing; Consumer Engagement; Brand Awareness; Influencer Marketing; Purchase Intention; Social Commerce; Shopee; Digital Consumer Behavior